The impact of collaborative atmosphere on innovative work behavior of college teachers, North China - Liu, Qian; Sun, Yu (Frontiers in Psychology, 2025)
Innovation and progress serve as the driving forces behind national development. Universities, with their comprehensive academic systems and robust research capabilities, undoubtedly play a crucial role in fostering student innovation and advancing faculty research innovation. This study aims to explore the relationship between the collaborative climate and innovative work behavior of university educators, as well as the mediating effect of knowledge sharing, in order to provide an important theoretical basis for universities to better promote innovative work behavior. This study adopts questionnaire survey method and semi-structured interview method. In the questionnaire survey stage, this study uses 473 in-service educators in colleges and universities as the research objects; in the interview stage, this study uses 8 in-service educators as the research objects. The results of the questionnaire study prove that educators’ cooperation atmosphere has a significant positive impact on innovative work behavior, educators’ collaborative climate has a significant positive impact on knowledge sharing, knowledge sharing has a significant positive impact on innovative work behavior, and knowledge sharing has a significant positive impact on teachers’ collaborative climate. There is a significant mediating effect on employees’ innovative work behavior. The interview results found that a positive collaborative climate within universities can influence teachers’ innovative work behavior through three channels: colleague support, management resource provision, and academic freedom encouragement. Therefore, a positive collaborative climate not only encourages communication and cooperation among faculty members but also inspires them to adopt and develop new methods and technologies in their research and teaching practices. Universities should place greater emphasis on enhancing their internal collaborative atmosphere.